Inhibiting MT2‐TFE3‐dependent autophagy enhances melatonin‐induced apoptosis in tongue squamous cell carcinoma. Issue 2 (11th January 2018) - Fan, Tengfei; Pi, Huifeng; Li, Min; Ren, Zhenhu; He, Zhijing; Zhu, Feiya; Tian, Li; Tu, Manyu; Xie, Jia; Liu, Mengyu; Li, Yuming; Tan, Miduo; et al.
Abstract: Autophagy modulation is a potential therapeutic strategy for tongue squamous cell carcinoma (TSCC). Melatonin possesses significant anticarcinogenic activity. However, whether melatonin induces autophagy and its roles in cell death in TSCC are unclear. Herein, we show that melatonin induced significant apoptosis in the TSCC cell line Cal27. Apart from the induction of apoptosis, we demonstrated that melatonin‐induced autophagic flux in Cal27 cells as evidenced by the formation of GFP‐LC3 puncta, and the upregulation of LC3‐II and downregulation of SQSTM1/P62. Moreover, pharmacological or genetic blockage of autophagy enhanced melatonin‐induced apoptosis, indicating a cytoprotective role of autophagy in melatonin‐treated Cal27 cells. Mechanistically, melatonin induced TFE3 (Ser321) dephosphorylation, subsequently activated TFE3 nuclear translocation, and increased TFE3 reporter activity, which contributed to the expression of autophagy‐related genes and lysosomal biogenesis. Luzindole, a melatonin membrane receptor blocker, or MT2 ‐siRNA partially blocked the ability of melatonin to promote mTORC1/TFE3 signaling. Furthermore, we verified in a xenograft mouse model that melatonin with hydroxychloroquine or TFE3 ‐siRNA exerted a synergistic antitumor effect by inhibiting autophagy. Importantly, TFE3 expression positively correlated with TSCC development and poor prognosis in patients. Collectively, we demonstrated that the melatonin‐induced increase in TFE3‐dependent autophagy is mediated through the melatonin membrane receptor in TSCC. These data also suggest that blocking melatonin membrane receptor‐TFE3‐dependent autophagy to enhance the activity of melatonin warrants further attention as a treatment strategy for TSCC.